Theoretical foundations efficient mass valuation of land - Koshel, A. (Land Management, Cadastre and Land Monitoring, 2017)
In the article the theoretical basis for determining the effectiveness of mass valuation of land in present-day conditions are described. The concept defenitsy effect and effectiveness as economic categories and their classification values for mass valuation of land are presented. The effectiveness of mass valuation of land in the settlements defines the structure of local budget and economic activities undertaken by local authorities on the basis of the results of the mass appraisal of real estate. Mass valuation is regular and it is characterized by high degree of standardization of procedures and a significant increase in the role of statistical methods for processing data related to the use of the most significant factors influencing the parameters of the object to its cost, as well as the need to determine the value of the objective laws change equivalent, which is only possible when using economic and mathematical methods and statistical analysis. Quality control results of mass valuation carried out principally in other ways, as obtained by applying statistical machine results can be checked as soon statistical methods. This shows the relevance of research topic and lack of elaboration for Ukraine problems of efficiency of mass land valuation.Scientific research conducted through the use of the dialectical method and techniques of abstraction, comparative analysis and synthesis, the article various models and methods of valuation of land for taxation purposes are analyzed. In addition, the group explored methods used, comparisons, and more. In economic theory and practice problems and determine the effect of efficiency aimed at profit is quite relevant. Economists consider cost-effectiveness, such as economic efficiency. In this case, the production can be attributed to the activities to conduct and organization of mass valuation of land. This pushes many different positions on criteria and indicators of economic efficiency, the composition of results and consideration of cost, given different definitions of efficiency and offered various ways to measure. The question of social, environmental and other efficiency are considered generally as elements that complement economic efficiency. For land evaluation work efficiency are the following types: economic (increase in tax collection and tax payments); ecological (removal of the negative impact on the earth, the environment); social (improvement of living conditions of the population in a particular area); information (identifying objects not previously recorded, increasing the number of taxpayers). Achieving economic or social effect due to the need for ongoing and one-time costs. The ongoing related costs included in cost of production. In order to improve the efficiency of monetary value of land mass based methods, in our view, to apply emergency measures to correct the situation in the monetary evaluation assessments, namely: - need to develop clear and understandable regulations for the implementation of mass land valuation, passage of expertise, information and other aspects of the implementation of inventory and evaluation work; - should develop new or significantly alter already existing methods so that they meet the requirements of international law, international standards of evaluation, and allow the user to understand the simple manufacturing process works; - appraiser who performs the mass appraisal should be fully independent and protected by law from public authorities. Key words: effect, efficiency, mass appraisal, land, classification.